Analysis of Balanced Nutrition Knowledge and Eating Habits of College Students - Kusmiyati, Kusmiyati; Ningtias, Anggun Cahya; Wulandari, Baiq Hesti; Aulia, Dian Ismi; Lestari, Sri Ayu (Jurnal Biologi Tropis, 2026)
Knowledge of balanced nutrition is a crucial factor influencing a person's eating habits. The purpose of this study was to identify balanced nutrition knowledge and eating habits among university students, thus providing a basis for effective education related to balanced nutrition guidelines. Respondents were Biology Education students at the Faculty of Teacher Training and Education, University of Mataram, who had never taken a Nutrition Science course and were willing to complete the questionnaire. Data on balanced nutrition knowledge were collected using a test, while data on eating habits were collected using a non-test instrument. Data collection used a Google Form, and data were analyzed descriptively, categorized as insufficient, sufficient, and good. The results showed that knowledge of balanced nutrition was categorized as good (64.1%), sufficient (33.3%), and insufficient (2.6%), while eating habits were categorized as good (25.6%), sufficient (64.1%), and insufficient (10.3%). Conclusions: 1). Most students' nutritional knowledge was categorized as good, while most students' eating habits were categorized as sufficient; 2). Education on balanced nutrition knowledge and eating habits is needed for students.